Differential effect of intermittent hypoxia and sleep fragmentation on PD-1/PD-L1 upregulation. Issue 5 (29th November 2019) - Cubillos-Zapata, Carolina; Almendros, Isaac; Díaz-García, Elena; Toledano, Victor; Casitas, Raquel; Galera, Raúl; López-Collazo, Eduardo; Farre, Ramón; Gozal, David; García-Rio, Francisco
Abstract: Immunosurveillance is compromised in patients with obstructive sleep apnea (OSA) as reflected by overexpression of the programmed death cell receptor and its ligand (PD-1/PD-L1) coinhibitory axis. However, the contributions of intermittent hypoxia (IH) and sleep fragmentation (SF) are unclear. We therefore evaluated the expression of PD-1 and PD-L1 on immune cells from mice subjected to IH or SF, and in human cells exposed to IH, oxidative stress, or both conditions. Six-week-old male C57BL/6J mice were exposed to either IH or SF using previously established in vivo models. Moreover, human peripheral blood mononuclear cells (PBMC) were cultured overnight under normoxia, IH, hydrogen peroxide (H2 O2 ), or both. Murine splenocytes and human PBMC were isolated, and labeled using surface-specific antibodies for flow cytometry analysis. Compared to control mice, IH induced higher expression of PD-L1 on F4/80 cells and of PD-1 on CD4 + and CD8 + T-cells, whereas no significant changes emerged after SF. In vitro models of IH and oxidative stress showed similar changes for expression of PD-L1 on human monocytes and PD-1 on CD4 + T-cells. Furthermore, H2 O2 increased PD-1 expression on CD8 + T-cells, compromising their cytotoxic capacity assessed by perforin expression, similar to IH. No evidence of synergistic effects was apparent. Therefore, PD-1/PD-L1 upregulation reported in patients with OSA appears to be preferentially mediated by IH rather than SF.